Analisis Strategi Bisnis Usaha Mikro Kecil Menengah Toko Kue (Studi Kasus Pada Toko Kue “Olahan Mey” Di Palangka Raya) - Muhammad Farras Nasrida; Lily Zahra Firdausya; Leli Astuti Gulo (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Bakery store business analysis is an attempt to understand the factors that affect the performance of a bakery store in a competitive market. In this analysis, several key factors such as the external environment, the internal environment, as well as social and cultural factors need to be taken into account. In bakery store business analysis, several analysis methods can be used such as SWOT analysis, Five Forces analysis, and market analysis. These methods can help the bakery store identify existing opportunities and challenges and find the right business strategy to optimize the performance and growth of the bakery store. By conducting proper business analysis, the bakery store can optimize its performance and increase profits. In addition, business analysis can also help the bakery store to stay competitive in an increasingly competitive market and adapt to changes.